Women leadership / Dr. Kardina Kamaruddin, Dr. Roziyana Jafri and Noor Malinjasari Ali - Kamaruddin, Kardina; Jafri, Roziyana; Ali, Noor Malinjasari (Universiti Teknologi MARA, Kedah, 2023)
Leadership remains an elusive phenomenon. Thus, it cannot be defined dispassionately. Leadership is value-laden and derives from how we make sense of leadership situations. Rost et al. (2005) stated that leadership is rational, management-oriented, male, technocratic, quantitative, cost-driven, hierarchical, short-term, pragmatic, and materialistic. Hagbert (2002), writing from a feminist perspective, viewed leadership as empowerment, which associated women with their abilities to influence others. Gender differences theories currently propose that men emerge as more task-oriented leaders than women. However, this is most likely in short-term groups. This because the tasks set involve a relatively superficial level of social interaction. On the other hand, women were found to emerge as social leaders more frequently than men. The introduction of gender difference theories signalled a change in the leadership literature as women’s behavior, abilities, and attitudes were considered, acknowledged, and evaluated (Jogolu & Wood, 2006). This is supported by contemporary studies on leadership that show that gender does matter for both how people respond to leaders and what leaders can bring to their roles (Goethals et al., 2017). The role of women in organizations and society has dramatically changed. Women are now seeking and obtaining positions of highest leadership in education, professions, and business. Globally, the proportion of women in senior management has increased from 31% to 32% (GrantThorton, 2022). In Malaysia, women currently make up 40% of positions in senior management teams within companies (TMR, 2022). Contexts represent women’s leadership. It refers to the setting in which leadership is developed and implemented. Context influences leaders’ actions, behaviors, and processes of leadership. Examining women and leadership from this angle entails looking at women leaders from both internal and external contexts. Firstly, psychological factors play a role in the challenges faced by women in leadership positions within organizations. Trailblazer or “first” in a leadership role can come with added pressure and challenges for women. They may face increased scrutiny and higher performance expectations as one of the few or the first women in a high-level position; resistance from colleagues and a lack of support; isolation and feelings of being an outsider; a lack of role models and mentorship; the burden of representing all women in the organization; and pressure to “break the glass ceiling” and pave the way for others (Chisholm-Burns et al., 2017). In addition, balancing assertiveness, and likability, refers to the challenge women leaders’ face in maintaining a delicate balance between being assertive and confident in their leadership style and being perceived as likeable and approachable by their peers, subordinates, and superiors. Women in leadership roles often face the stereotype that assertive women are seen as bossy, aggressive, or unlikable, while women who are too accommodating or passive may be seen as weak or ineffective (Costinhas, 2022; Manian & Sheth, 2021). To effectively balance assertiveness and likability, women leaders may need to develop self-awareness and communication skills that enable them to assert themselves confidently while maintaining their interpersonal relationships and reputation (Maseko, 2013).